2023
DOI: 10.1063/5.0140843
|View full text |Cite
|
Sign up to set email alerts
|

3D structured Bessel beam polarization and its application to imprint chiral optical properties in silica

Abstract: Polarization plays a crucial role in light–matter interactions; hence its overall manipulation is an essential key to unlock the versatility of light manufacturing, especially in femtosecond laser direct writing. Existing polarization-shaping techniques, however, only focus on their manipulation in the transverse plane of light beams, i.e., two-dimensional control. In this paper, we propose a novel passive strategy that exploits a class of femtosecond laser written space varying birefringent elements to shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In view of the high price of InGaAs detectors, it has been proposed to use low-cost silicon photomultiplier tube (SiPM) detectors instead, and the price of the detector module is only a few tenths of the InGaAs detectors while obtaining similar imaging results [19]. In microscopy, there have also been many studies that have reported improved lateral resolution by using a non-diffractive beam [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the high price of InGaAs detectors, it has been proposed to use low-cost silicon photomultiplier tube (SiPM) detectors instead, and the price of the detector module is only a few tenths of the InGaAs detectors while obtaining similar imaging results [19]. In microscopy, there have also been many studies that have reported improved lateral resolution by using a non-diffractive beam [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Additionally, beams featuring polarization states that evolve during propagation have enabled the fabrication of chiral structures within the bulk of fused silica. [12] Optical vortices have also emerged as effective tools for manipulating laser-matter interaction. In Gaussian laser beams, the phase singularity is responsible for doughnut-shaped crosssections.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,11 ] Additionally, beams featuring polarization states that evolve during propagation have enabled the fabrication of chiral structures within the bulk of fused silica. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%